miRNome of Child A hepatocellular carcinoma in Egyptian patients - EL-shqnqery, Hend E.; Mohamed, Rania Hassan; Samir, Omar; Ayoub, Islam; El-Sayed, Wael M.; Sayed, Ahmed A. (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) has different etiologies that contribute to its heterogeneity. In regards to the number of HCC patients, Egypt ranks third in Africa and fifteenth worldwide. Despite significant advancements in HCC diagnosis and treatment, the precise biology of the tumor is still not fully understood, which has a negative impact on patient outcomes. Advances in next-generation sequencing (NGS) have increased our knowledge of the molecular complexity of HCC. In this research, 16 HCC and 6 tumor adjacent tissues (control) of Child A Egyptian patients were successfully profiled for the expression profile of miRNAs by NGS. Forty-one differentially expressed miRNAs (DEMs) were found by differential expression analysis, with 31 being upregulated and 10 being downregulated. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis was then conducted on these differentially expressed miRNAs revealing that Sensitivity and specificity analysis showed that hsa-miR-4488, hsa-miR-3178, and hsa-miR-3182 were unique miRNAs as they are expressed in HCC tissues only. These miRNAs were all highly involved in AMPK signaling pathways. However, hsa-miR-214-3p was expressed in control tissues about eight times higher than in cancer tissues and was most abundant in “pathways in cancer and PI3K-Akt signaling pathway” KEGG terms. As promising HCC diagnostic markers, we here suggest hsa-miR-4488, hsa-miR-3178, hsa-miR-3182, and hsa-miR-214-3p. We further urge future research to confirm these markers' diagnostic and prognostic potential as well as their roles in the pathophysiology of HCC.